Phytochemical Analysis and Comparative Effect of Cinnamomum zeylanicum Piper nigrum and Pimpinella anisum with Selected Antibiotics and Its Antibacterial Activity against Enterobacteriaceae Family - Shiney ramya, B (International Journal of Pharmaceutical & Biological Archive, 2012)
Phytochemical Analysis and Comparative Effect of Cinnamomum zeylanicum Piper nigrum and Pimpinella anisum with Selected Antibiotics and Its Antibacterial Activity against Enterobacteriaceae Family